2022
DOI: 10.3389/fphar.2022.921612
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation Involved in Diabetes-Related Pain and Itch

Abstract: Diabetes mellitus (DM) is a global epidemic with increasing incidence, which results in diverse complications, seriously affects the patient quality of life, and brings huge economic burdens to society. Diabetic neuropathy is the most common chronic complication of DM, resulting in neuropathic pain and chronic itch. The precise mechanisms of diabetic neuropathy have not been fully clarified, hindering the exploration of novel therapies for diabetic neuropathy and its terrible symptoms such as diabetic pain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 170 publications
0
14
0
Order By: Relevance
“…In addition, diabetes mellitus (DM)‐induced increases in advanced glycosylation products in dermal collagen and skin ageing in the elderly may both lead to reduced hydration of the stratum corneum and cause dry skin followed by pruritus. Complications of peripheral neuropathy in elderly diabetic patients may also lead to the impaired barrier function of the skin, resulting in sensory dysfunction of cutaneous nerve endings of C fibres, leading to abnormal discharge of sensory C nerve fibres and causing pruritus 20 . Peripheral nerve injury can result in sensory abnormalities accompanied with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diabetes mellitus (DM)‐induced increases in advanced glycosylation products in dermal collagen and skin ageing in the elderly may both lead to reduced hydration of the stratum corneum and cause dry skin followed by pruritus. Complications of peripheral neuropathy in elderly diabetic patients may also lead to the impaired barrier function of the skin, resulting in sensory dysfunction of cutaneous nerve endings of C fibres, leading to abnormal discharge of sensory C nerve fibres and causing pruritus 20 . Peripheral nerve injury can result in sensory abnormalities accompanied with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Both ALA and vitamin E modulate upstream enzymes responsible for the disinhibition of NF-κB, thereby preventing its activation [ 89 ]. Avoiding NF-kB activation is possibly the mechanism by which ALA has been shown to reduce neuroinflammation markers in vitro [ 90 ], considering that NF-kB is an important transcription factor associated with glial activation and transcription of pro-inflammatory cytokines such as TNF-α and IL-1β, which lead to spinal neuroinflammation and increased ROS production [ 91 ].…”
Section: Antioxidant Potential Of Alpha-lipoic Acid In Neuropathic Painmentioning
confidence: 99%
“…Besides, 66.6% of patients reported that linezolid-induced pain was mainly in the feet (Figure 1D). This led us to consider that linezolid caused clinical symptoms similar to diabetic peripheral neuropathy (DPN) (Liu J. et al, 2022;Fang, Wang, Song, Wang, & Zhang, 2022).…”
Section: Clinical Information Collectionmentioning
confidence: 99%